Autocrine expression of hepatocyte growth factor and its cytoprotective effect on hepatocyte poisoning - He, Yong (World J Gastroenterol, 2004)
AIM: To construct pEGFP-hepatocyte growth factor (HGF) expression vector, the to detect its expression in transfected human hepatocytes, and to investigate the influence of autocrine HGF expression on the proliferative potential and cytoprotective effects in human hepatocytes. METHODS: Human HGF cDNA was ligated to the pEGFP vector. Recombinant plasmid was transfected into human hepatocyte line QZG with liposome. Expression of HGF protein was observed by fluorescence microscopy and immunohistochemistry. Hepatic cells were collected 24, 48, and 72 h after transfection to detect the number of [(3)H]-TdR uptake in DNA. DNA synthesis was observed by using PCNA stain immunohistochemistry. Acute liver cell damage was induced by carbon tetrachloride. Cytoprotective effect was observed by examining the survival rate of hepatocytes and leakage of intracellular alanine transaminase (ALT) and potassium ions. RESULTS: HGF identification of pEGFP-HGF by enzyme digestion showed that HGF fragment was cloned into BamH I and Sal I sites of pEGFP-N3. Expression of GFP in transfected hepatocytes was observed with fluorescence microscopy. The [(3)H]-TdR uptake became 7 times as many as in the control group 96 h after transfection. After HGF transfection, the survival rate of hepatocytes poisoned by CCl(4) significantly increased (83% vs 61%, P < 0.05), and the leakage of intracellular alanine transaminase and potassium ions decreased (586 nkat/L vs 1089 nkat/L, P < 0.01; and 5.59 mmol/L vs 6.02 mmol/L, P < 0.01 respectively). Culture of transfected hepatic cells promoted the proliferation of other non-transfected cells. CONCLUSION: Transfected HGF is expressed in hepatic cells and has the activity of promoting cell division and protecting hepatic cells against poisoning.